Analisis Usability Pada Aplikasi Mytelkomsel Menggunakan Metode Importance Performance Analysis Terhadap Kepuasan Pengguna - Ester Pardede; Sharipuddin; Hartiwi, Yessi (LPPM STIKOM Dinamika Bangsa, 2024)
The MyTelkomsel application is an alternative for Telkomsel cellular provider users. Therefore, the application is expected to have a good level of usability for its users. However, there are still users who complain and feel dissatisfied with the services in the MyTelkomsel application. Therefore it is necessary to measure the usability of the MyTelkomsel application. This study discusses the results of usability analysis on the MyTelkomsel application based on the results of data collection from questionnaires distributed to 152 respondents who are users in the Jambi City Community. This study uses the Importance Performance Analysis (IPA) method by analyzing Usability with 5 variables: (Learnability, Efficiency, Satisfaction, Error, Memorability) as a reference for the question indicators used in the research questionnaire using the Likert scale and the Importance Performance Analysis (IPA) method. which is used to analyze the results of the data based on the 4 quadrants of the IPA Cartesian diagram. The data was collected by distributing a questionnaire containing 24 questions to 152 respondents who are users of the Mytelkomsel application. In this study, all dimensions have a significant impact on the deepend variables except the fulfillment dimension.